In silico analysis of Kemukus (Piper cubeba) as an antidyspeptic through inhibition of histamine H₂ receptors (3UZE) - Popy Meylani,; Satriawan, Herland (SAINSTEK International Journal on Applied Science, Advanced Technology and Informatics, 2025)
Dyspepsia is strongly associated with excessive gastric acid secretion mediated by histamine H₂ receptors. Natural products such as Piper cubeba have long been used to alleviate digestive disorders, yet their molecular mechanisms remain underexplored. This study aimed to evaluate the antidyspeptic potential of ten major compounds from P. cubeba through in silico docking against the histamine H₂ receptor structure (3UZE), with ranitidine as a positive control. Molecular docking was performed to predict binding affinity and interaction profiles within the receptor’s active site. Several cubeb constituents demonstrated favorable binding energies and key interactions comparable to the standard ligand, suggesting potential inhibitory activity. These findings provide preliminary evidence that P. cubeba bioactive compounds may act as histamine H₂ receptor modulators and support their further investigation as natural antidyspeptic candidates.